An updated classification of cyanobacterial orders and families based on phylogenomic and polyphasic analysis - Strunecký, Otakar; Ivanova, Anna Pavlovna; Mareš, Jan (Journal of phycology, 2023)
Cyanobacterial taxonomy is facing a period of rapid changes thanks to the ease of 16S rRNA gene sequencing and established workflows for description of new taxa. Since the last comprehensive review of the cyanobacterial system in 2014 until 2021, at least 273 species in 140 genera were newly described. These taxa were mainly placed into previously defined orders and families although several new families were proposed. However, the classification of most taxa still relied on hierarchical relationships inherited from the classical morphological taxonomy. Similarly, the obviously polyphyletic orders such as Synechococcales and Oscillatoriales were left unchanged. In this study, the rising number of genomic sequences of cyanobacteria and well-described reference strains allowed us to reconstruct a robust phylogenomic tree for taxonomic purposes. A less robust but better sampled 16S rRNA gene phylogeny was mapped to the phylogenomic backbone. Based on both these phylogenies, a polyphasic classification throughout the whole phylum of Cyanobacteria was created, with ten new orders and fifteen new families. The proposed system of cyanobacterial orders and families relied on a phylogenomic tree but still employed phenotypic apomorphies where possible to make it useful for professionals in the field. It was, however, confirmed that morphological convergence of phylogenetically distant taxa was a frequent phenomenon in cyanobacteria. Moreover, the limited phylogenetic informativeness of the 16S rRNA gene, resulting in ambiguous phylogenies above the genus level, emphasized the integration of genomic data as a prerequisite for the conclusive taxonomic placement of a vast number of cyanobacterial genera in the future.
Keywords: genom; sekvenční analýza DNA; Cyanobacteria; Sequence Analysis, DNA; RNA, Ribosomal, 16S; Cyanophyceae; RNA ribozomální 16S; 16S rRNA; Vampirovibriophyceae; taxonomy; polyphasic approach; sinice; fylogeneze; Phylogeny; multilocus; Genome; phylogenomic